THE VALUATION OF FIXED ASSETS. - Daniels, M. B. (The Accounting Review, 1933)
Abstract The article focuses on valuation of fixed assets. The values of assets might be determined from the equities. Stock exchange quotations provide current values of stocks and of bonds. The total value of all capital stock in the hands of the public plus the face value of bonds and other liabilities would give a figure which might be called the value of the corporation. Another approach to the determination of asset values would be through the process of capitalizing normal earnings. This is a valuation method of ultimate importance in the field of unregulated industry. Still another possible approach to the valuation of a corporation's assets is the one ordinarily taken; an appraisal is made of the assets themselves. Cost is the logical and preferable basis for balance-sheet valuation of plant and equipment. Deviation from cost results in distortion of future income and earned surplus. The belief that asset values of plant and equipment as shown on the balance sheet indicate market value or any other value should be discouraged. They should represent legitimate unrecovered costs, long-term prepaid expenses, and in this way display the financial condition of the individual enterprise in question.